PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN (SAP), PEMANFAATAN TEKNOLOGIINFORMASI DAN KOMITMEN ORGANISASI TERHADAP NILAI INFORMASI PELAPORAN KEUANGAN ORGANISASI PERANGKAT DAERAH (OPD) DI KABUPATEN BADUNG - Anak Agung Istri Diah Endiyani; Anak Agung Ketut Agus Suardika; Putu Nuniek Hutnaleontina (UNHI Press, 2021)
This study aims to determine the effect of implementing Government Accounting Standards (SAP), Utilization of Information Technology and Organizational Commitment on the Value of Information on Regional Apparatus Organization Financial Reporting (OPD) in Badung Regency. This research was conducted at 38 Regional Apparatus Organizations in Badung Regency. Data collection methods in this study used a survey method with a questionnaire. The sample used in this research is the Head of Sub Division of Finance, Bookkeeping and Treasurer in each Regional Apparatus Organization, who have a tenure of more than one year, totaling 114 people. The sampling method used was purposive sampling method. The data analysis method used in this research is multiple linear regression analysis. Based on the results of the analysis, this study shows that the application of Government Accounting Standards (SAP), Utilization of Information Technology and Organizational Commitment has a positive effect on the Value of Information on Financial Reporting of Regional Apparatus Organizations (OPD) in Badung Regency.